Management of carcinoma rectum in a tertiary care centre in Assam - Raju, Likha; Ronya, Rejum (International Journal of Research in Medical Sciences, 2022)
Background: Rectal cancer is one of the frequent human malignant neoplasms and the second most common cancer in large intestine. Colorectal cancers, as one of the major public health problems, is the third most common cancer in men and the second in women in the world with a lifetime probability of 4.7-5%. It has been reported as the third leading cause of death in men and women in the United States. Methods: The study comprised of 40 cases of carcinoma rectum admitted in the seven surgical units of the department of surgery, Assam medical college and hospital, Dibrugarh, for a period of 1 (one) year from 2018 to 2019. The patients were selected based on the clinically suspected cases of carcinoma rectum and confirmation made upon by histopathological examinations and the necessary investigations. The patients were staged according to the TNM staging system. Results: A total of 40 patients examined. In 34 of the total 40 patients (85%), the growth could be felt per rectally and sigmoidoscopic biopsy where taken which confirmed the diagnosis. In our study, 26 (65%) patients belonged to the stage III correlating with their late presentation, 10 (25%) stage II and 5 % in stage I and IV. The surgical management varied according to the presentation and the status of the patient. Conclusions: In conclusion, a good clinico-pathological work-up in addition with adequate wide range of appropriate diagnostic interventions usage resulted in early diagnosis and timely surgical interventions and the necessary adjuvant therapies.